2009
DOI: 10.2514/1.30013
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Nanoadhesive Bonding of Space-Durable Polymer and Its Performance Under Space Environments

Abstract: The present investigation highlights fabrication of polybenzimidazole by high-performance nanoadhesive and its performance under space environments. High-performance nanoadhesive is prepared by dispersing silicate nanopowder into ultra-high-temperature-resistant epoxy adhesive. The surface of polybenzimidazole is ultrasonically cleaned by acetone and then modified by low-pressure plasma before bonding. Electron spectroscopy for chemical analysis reveals that the polymer surface becomes hydrophilic, resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…From experiments, it was concluded that quartz nanoparticles not only increased the sensitivity of damage monitoring, but also enhanced the static and fatigue joint strengths. Bhowmik et al [223] investigated the fabrication of polybenzimidazole by high-performance nanoadhesive and studied its performance under space environments. From thermogravimetric analysis, it was shown that the cohesive properties of nanoadhesive were more stable when heated up to 350 • C. They found an increase in the adhesive joint strength of surface modified polybenzimidazole and a further significant increase in joint strength when it is prepared by nanosilicate epoxy adhesive.…”
Section: Nanoadhesivesmentioning
confidence: 99%
“…From experiments, it was concluded that quartz nanoparticles not only increased the sensitivity of damage monitoring, but also enhanced the static and fatigue joint strengths. Bhowmik et al [223] investigated the fabrication of polybenzimidazole by high-performance nanoadhesive and studied its performance under space environments. From thermogravimetric analysis, it was shown that the cohesive properties of nanoadhesive were more stable when heated up to 350 • C. They found an increase in the adhesive joint strength of surface modified polybenzimidazole and a further significant increase in joint strength when it is prepared by nanosilicate epoxy adhesive.…”
Section: Nanoadhesivesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] They have been found useful in applications ranging from flame-resistant fabrics to aerospace materials and fuel cell membranes. [10][11][12][13][14][15][16] Fully aromatic poly[2,2-(m-phenylene)-5,5-bibenzimidazole] or meta-PBI (m-PBI) (Scheme 1) is the most common commercially available PBI polymer. In addition to m-PBI, different types of PBIs are prepared by using various Molecular layer deposition (MLD) [27][28][29][30][31][32][33][34][35] is a vapor phase thin film deposition method with similar characteristics as atomic layer deposition (ALD).…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–9 ] They have been found useful in applications ranging from flame‐resistant fabrics to aerospace materials and fuel cell membranes. [ 10–16 ] Fully aromatic poly[2,2‐( m ‐phenylene)‐5,5‐bibenzimidazole] or meta‐PBI (m‐PBI) ( Scheme ) is the most common commercially available PBI polymer. In addition to m ‐PBI, different types of PBIs are prepared by using various aliphatic or aromatic derivatives as monomers for optimizing application specific properties for bioactive materials and fuel cell membranes, for example.…”
Section: Introductionmentioning
confidence: 99%